The Council of Bars and Law Societies of Europe as a driver for the formation of unified standards of the bar in the law of the European Union - Shchepaniuk, Yurii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
This article explores the role of the Council of Bars and Law Societies of Europe (CCBE) in shaping unified standards for the legal profession within the European Union. The CCBE is a key player in promoting the harmonization of legal practices across EU member states. The article discusses the historical development and evolution of the organization, which was founded in 1960, as well as its primary functions and objectives, such as protecting the rights of lawyers, advancing professional standards, and ensuring access to justice. The article emphasizes CCBE’s significant impact on the European legal landscape, particularly in its efforts to create a unified legal space that allows lawyers to offer legal services across EU borders without legal barriers. The CCBE actively contributes to the development of European legal norms, working closely with EU institutions to influence legislative changes affecting the legal profession. This includes areas such as the recognition of professional qualifications, the legal status of lawyers, and the establishment of ethical guidelines for the legal profession. The article also highlights the organization’s work in fostering international cooperation among legal practitioners through its committees and plenary sessions, which facilitate the exchange of knowledge and best practices among lawyers from different EU countries. These sessions also serve as a platform for the discussion of key issues such as human rights, the rule of law, and democratic values. Furthermore, CCBE plays a vital role in supporting the continuous education of lawyers, ensuring that legal professionals in Europe maintain high standards of competence and stay up-to-date with evolving legal frameworks. The article concludes that the CCBE is essential in strengthening the rule of law within the EU by uniting the legal community, promoting access to justice, and ensuring the protection of human rights across European borders.